On-farm validation of nutrients response in different locations of Maharashtra and Andhra Pradesh - Kokate, K D; Reddy, G Rajender; Sudhakar, N (The Indian Journal of Agricultural Sciences, 2012)
On-farm trials (OFTs) and verification trials (VTs)/frontline demonstrations (FLDs) were conducted in Maharashtra and Andhra Pradesh to assess the performance of crops with recommended fertilizer application based on soil test values for predominant crops grown under different farming situations. During 2005–06 to 2009–10, a total of 1 492 different trials were conducted in different farming situations. The OFTs and VTs were conducted in a participatory mode incorporating the farmers’ perceptions. The results obtained from the large-scale trials conducted across the states revealed that substantial increase in yield of grain and oilseed crops was obtained by application of fertilizers as recommended which supplied balanced nutrition over the yield obtained with farmers’ practice of imbalanced fertilization. The yield was further enhanced when fertilizer was applied based on soil test values. The present study will help to obtain the achievable yields of different crops as the trials were conducted under on-farm conditions with farmers’ management systems.